Influences of education on gender and status: a study of Sri Lankan export processing zone workers. (2015) - Hancock, Peter; Carastathis, Geoff; Georgiou, Jonathan; Adibi, Hossein
Sri Lankan women employed by export processing zones (EPZs) represent various educational levels. Using a survey sample of 2, 304 randomly selected female EPZ workers, this paper quantitatively compared workers with ordinal-level secondary education - O-levels - and below (n = 1, 423) - and those with advanced-level secondary education - A-levels - and above (n = 878). Overall, the 'higher educated' women reported more positive socio-economic outcomes than their 'lower educated' counterparts. Mann-Whitney U tests demonstrated greater earning (saving) capacities among 'higher educated' women; with Pearson's chi-square test of contingencies revealing that this cohort were also more likely to receive promotions than 'lower educated' women. Although reports of abuse (harassment) were generally low among both sub-samples, 'lower educated' female EPZ workers were more likely to experience verbal abuse, sexual harassment and public humiliation. Despite such inter-group polarisation, a near consensus of all participants reported feeling greater empowerment as a result of their time in formal employment.